KEADILAN HUKUM ANAK KORBAN TINDAK PIDANA KEKERASAN SEKSUAL DI KABUPATEN KENDAL - Kismanto Kismanto; Anis Mashdurohatun (Jurnal Hukum Khaira Ummah, 2017)
Background in this study cases of abuse of children aged under 12 years. PPA investigators (Protection of Women and Children) in handling the case are guided by Law no. 11 Year 2012 on Child Criminal Justice System. In the judicial system, it encourages the process of diversion and restorative justice. The formulation of this journal issue: (1) what is the legal protection for the child as a victim; (2) problematic of legal protection for child as victim; (3) legal justice model for children as victims of sexual violence crimes with child offenders under 12 years old based on restorative justice in Kendal District. The purpose of this study is to understand: (1) legal protection for children as victims; (2) legal protection problems for children as victims: (3) legal justice model for children as victims of sexual violence crimes with child offenders under 12 years old based on restorative justice in Kendal district. To collect data, the authors use interview techniques with guided free techniques. The results of this study are: (1) legal protection for children as victims of sexual violence criminal acts that all decision-making should always consider the survival and growth of children. The current regulation is deemed not to consider justice from the side of the victim maximally applicable to law enforcement practices so that the child as victim does not get legal protection or justice optimally. (2) the problem of legal protection for children as victims of sexual violence including law norms regulating the criminal justice system of children is not sufficient in responding sociology societal development exposed to progress of science and technology (Internet). The proof of law enforcers make discretionary decisions (legal policies) that adjust to the development of sociology of society. (3) the justice model for children as victims of criminal acts transformed from restorative changes into substantive justice format. That is how victims and families of victims really feel fair. A sense of justice that meets the victim's needs such as future compensation for the victim and the alienation of the perpetrator from the neighborhood of the abusive victim. Legal protection is a fulfillment of a sense of justice for children on social dimensions, emotional and paedegogis children. Keywords: Legal Protection, Child in Law, Diversi,Restorative